2012
DOI: 10.1016/j.mayocp.2011.12.021
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Acid Suppression and Outcomes in Clostridium difficile Infection: A Population-Based Study

Abstract: Objective: To evaluate the association of gastric acid suppression medications, including proton pump inhibitors and histamine type 2 blockers, with outcomes in patients with Clostridium difficile infection (CDI) in a population-based cohort. Patients and Methods: To understand the association between acid suppression and outcomes in patients with CDI, we conducted a population-based study in Olmsted County, Minnesota, from January 1, 1991, through December 31, 2005. We compared demographic data and outcomes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
3
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 40 publications
4
45
3
4
Order By: Relevance
“…This is consistent with other studies using a similar definition for C. difficile complication [6,9,10]. The population was mainly hospitalized elderly patients with numerous comorbidities, frequent exposure to antimicrobials, acid suppression, and infected predominantly with the R027 strain.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with other studies using a similar definition for C. difficile complication [6,9,10]. The population was mainly hospitalized elderly patients with numerous comorbidities, frequent exposure to antimicrobials, acid suppression, and infected predominantly with the R027 strain.…”
Section: Discussionsupporting
confidence: 90%
“…49,50 Furthermore, studies have found that after controlling for important confounders, the use of PPIs and histamine 2 blockers was not associated with the risk of CDI 51 or adverse outcomes from CDI. 52 Thus, it is not clear whether use of acid-suppressing drugs is an independent risk factor for CDI, 53 although the US Food and Drug Administration (FDA) has recently issued a warning that PPIs are associated with an increased risk of CDI. A summary of risk factors for CDI is given in Table 1.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Despite these results, the most recent studies offer conflicting viewpoints as to the association between PPI use and increased risk of C. difficile infection. These studies showed that while univariate analysis may show a statistically significant relationship between PPI use and CDI, multivariable analysis reveals no significant relationship [27][28][29] . Further, the most recent review on detection, prevention and treatment of C. difficile does not include restriction or avoidance of PPIs in the recommendations for prevention of C. difficile infection [30] , nor is this recommended by multi society clinical practice guidelines [31] .…”
Section: Risk Factors For CDImentioning
confidence: 99%